2012
DOI: 10.1111/j.1365-2672.2012.05371.x
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of verticillium wilt and colonization of cotton plants by an endophytic bacterial isolate

Abstract: Aims To explore biocontrol potential of 39 DAEB isolates (doubly antagonistic towards both Verticillium dahliae Kleb and Fusarium oxysporum) against verticillium wilt of cotton and to elucidate colonization and category characteristics of an endophytic bacterium with significant biocontrol activity. Methods and Results Thirty‐nine antagonistic endophytic bacteria strains were tested for their ability to control verticillium wilt in cotton plants caused by a defoliating pathotype of V. dahliae 107 in cotton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Further, treatment with Pseudomonas spp., T. virens or Enterobacter sp. HA02 decrease wilt incidence and improve cotton growth parameters (Hanson, 2000;Erdogan and Benlioglu, 2010;Li et al, 2012). Similarly, mycorrhizal fungi of Glomus spp.…”
Section: Referencesmentioning
confidence: 97%
“…Further, treatment with Pseudomonas spp., T. virens or Enterobacter sp. HA02 decrease wilt incidence and improve cotton growth parameters (Hanson, 2000;Erdogan and Benlioglu, 2010;Li et al, 2012). Similarly, mycorrhizal fungi of Glomus spp.…”
Section: Referencesmentioning
confidence: 97%
“…and Serratia plymutica , have been shown to be effective antagonists of Verticillium wilt [78]. Recent studies have indicated that endophytes colonize the internal tissues of plants and can improve plant growth and plant health [911]. …”
Section: Introductionmentioning
confidence: 99%
“…Page 7 of 28 A c c e p t e d M a n u s c r i p t 7 The inhibition of biofilm formed by P. aeruginosa PAO1was tested using microtiter plate assay [19] with some modifications. Briefly, P. aeruginosa PAO1 was grown at 37 ºC for 18 h in tryptic soy broth (TSB, Himedia, India).…”
Section: Antibiofilm Assay By Microtiter Plate Methodsmentioning
confidence: 99%
“…Endophytes are known to colonize internal tissues of the plants without causing disease and said to be endosymbionts [7]. The endophytic bacterial population within plant reflects the great genetic and metabolic diversity.…”
Section: Page 3 Of 28mentioning
confidence: 99%